الحركة الانفصالية في نيجيريا (1967- 1970م - قرين, عبد الكريم (جامعة الوادي University of Eloued, 2016)
إن السياسة البريطانية الاستعمارية في نيجيريا، كانت أساس الصراع الذي عانته هذه البلاد بعد الاستقلال، وفي إطار السياسة البريطانية برزت هوة واسعة بين أوضاع الإقليم الشمالي من ناحية، وأوضاع الإقليم الجنوبي من ناحية أخرى. ولعل أكثر المؤشرات دلالة على مدى تأثيرات التناقضات القبلية على البيئة الاجتماعية والسياسية في نيجيريا، هي الأسس القبلية لهده الأزمة، والواقع أن هذه الاعتبارات القبلية والطبقية، كانت أحيانا تجتمع وفي تداخلها تمهد المناخ لسلسلة من الانقلابات العسكرية. بداية من عام 1966م، وظلت تتكرر في الحياة السياسية النيجيرية وكان آخرها الانقلاب الذي اغتيل فيه الجنرال مورطاله يوم 13فيفيري1976م ، فهذه المسائل هي التي أصبحت لب الأزمة النيجيرية، وخاصة بعد اجتماع أيورى. أما مواقف بعض الدول والمنظمات العالمية والدولية والإقليمية، دوافع متنوعة، كما حدثت تغيرات وتذبذب في مواقف بعض الدول ، وقد أيدت معظم الدول الإفريقية حكومة نيجيريا في موقفها من أوجوكو، فموضوع الانفصال بصفة عامة، موضوع كريه عند اغلب الدول الإفريقية خصوصا تلك التي يهددها شبح الانفصال دائما، وهي كثيرة في القارة. The British colonial policy in Nigeria, was the basis of the conflict suffered by this country after independence, in the context of British politics emerged a wide gap between the Northern Territory conditions on one hand, and the status of the southern region on the other. Perhaps the most indicators signify the extent of tribal contradictions effects on the social and political environment in Nigeria, are the foundations of this topic Tribal crisis, and the fact that these considerations tribal and class, sometimes they meet in overlapping pave the climate of a series of military coups. Beginning in 1966, and has been repeated in the Nigerian political life and the most recent coup in which Gen. Mortalh assassinated on 13 Veveri 1976, these are the issues that have become the core of the Nigerian crisis, especially after Iori meeting. The positions of some countries and international, regional and international organizations, a variety of motives, as there have been changes and the fluctuation in the positions of some countries, most African countries supported the Government of Nigeria in the position of Ojukwu, The subject of secession in general, distasteful subject when most African countries, especially those that are threatened by the specter of secession always, they are many in the continent.
Keywords: نيجيريا، الحركة الانفصالية، الأزمة النيجيرية